Knowledge gap and earnings differential in the knowledge-based economy - Cheng, Ming Yu; Ghulam, R. (ROUTLEDGE JOURNALS, 2007)
This article examines the effect of the 'quantity' and 'quality' of education on earnings. The 'quantity' of education is measured by the level of the highest education attained while the 'quality' of education is determined by degree of the knowledge gap between knowledge acquired in school and skills required in the work place.